SOCIAL CONSCIOUSNESS AS A SUBJECT OF PHILOSOPHY AND THE HUMANITIES - T. V. Panfilova (Концепт: философия, религия, культура, 2017)
Social consciousness studies are essential to humanities provided by the university program. This is of particular importance as a part of the philosophical course since only philosophy regards social consciousness as a whole system. Forms and levels of social consciousness are in the foreground. Each form is stressed to be manifested at all levels although to different degrees. The status of science remains controversial. Scientific consciousness and ordinary consciousness must be distinguished. It is rather difficult for students and post-graduates to understand what social psychology means and what kind of role it plays in public life. Ideology takes a special place in social consciousness structure. We should pay particular attention to it. Correlation between social, group and individual consciousness is a serious problem. Learning of this theme is of educative and practical importance. It favors the skills of joint activity in students' group encouraging to overcome fragmentariness typical of some young people consciousness and to form consistent thinking in its turn. We should dwell on the question of values both on theoretical and practical levels. The concept of a possible conflict of values is of great practical importance. On the one hand modern person is engaged in global processes and shares "all-human" values, on the other - being grown up in some ethno-cultural environment he shares the values of the ethnic group. Trying to solve the intrapersonal conflict, students form creative attitude to education and upbringing. Comprehension of what values are and why they clash with each other will help students to become subjects of intercultural interaction. The question of what humanism is and how to put it into practice will be raised over again.